MODERN TREATMENT OF INTESTINAL HELMINTOSES IN CHILDREN - Аrashova Gulnora Amirkulovna (Web of Journals Publishing, 2025)
In this article, we have evaluated the diagnostic methods of helminthiasis with an extensive review of literature, electronic databases and books. The search covered articles published up to 2022 and some textbooks. It was concluded that the combination of traditional microscopy with the stool concentration method should still be performed in a routine medical laboratory due to its economic and high sensitivity and immunologically based analysis and molecular methods, which are recommended to be used as additional tests to the traditional technique.
Keywords: Helminthiasis, diagnostics, methods, metronidazole.